PERBEDAAN IPSS, Q MAX, DAN VOLUME PROSTAT PADA PEMBERIAN KOMBINASI INHIBITOR 5α-REDUKTASE (DUTASTERIDE) DAN ANTI ESTROGEN (TAMOXIFEN) PADA PASIEN BPH YANG MENGALAMI LUTS TANPA KOMPLIKASI - Seputra, Kurnia Penta; Soetojo, Soetojo; Soebadi, Doddy M (Indonesian Journal of Urology, 2008)
Objective: To compare the IPSS, Q max, and volume of the prostate pre and post treatment of 5α-reductase inhibitor and tamoxyfen in patients with BPH. Material and Methods: We collected 40 patients who had been diagnosed as BPH without urine retention. They were classified in to 4 groups, each group contained of 10 patients who were given tamoxifen, dutasteride, combination tamoxyfen with dutasteride, or placebo. We recorded IPSS, uroflow, and volume of the prostate before and after 3 months of medication. Data were analyzed by the SPSS 12 program. Results: Q max (7,75 + 3,5538 to 9,15 + 2,9448) and IPSS (z score –1,633) after treatment with tamoxyfen (p > 0,05) was not improved. We found significant decrease of the prostate volume (40,124 + 7,9129 to 36,323 + 8,2573) after treatment with tamoxifen (p < 0,05). There is significant improvement of Q max (9,55 + 3,2793 to 15,12 + 4,3522), IPSS (z score –2,887), and significant decrease of the prostate volume (30,93 + 9,0031 to 24,506 + 7,3267) after treatment with dutasteride (p < 0,05). There was also significant improvement of Q max (6,55 + 2,5435 to 8,86 + 4,4475), IPSS (z score –2,449), and decrease of prostate volume (31,403 + 9,0031 to 26,78 + 7,3267) after treatment with the combination dutasteride and tamoxifen (p < 0,05). None of those parameters were improved in placebo group. Conclusion: Q max and IPSS improve significantly in the dutasteride and the combination group. There was a significant decrease of the prostate volume in all groups except the placebo group.